AgileMultiIdeogram: Rapid Identification and Visualization of Autozygous Regions Using Illumina Short-Read Sequencing Data - Christopher M. Watson; Carolina Lascelles; Morag Raynor; Marilena Elpidorou; Ummey Hany; Laura Crinnion; Colin A. Johnson; Eamonn Sheridan; Alexander F. Markham; James A. Poulter; David T. Bonthron; Ian M. Carr (Biology)
Rare autosomal recessive diseases are a major cause of mortality and morbidity. They occur more frequently in individuals with consanguineous parents, in which case the pathogenic variants are often located within regions of genetic identity by descent. A well-established and effective way of identifying these “autozygous” genomic regions has been to search for runs of homozygous genotypes in microarray SNP data. However, with the widespread use of whole-genome and exome sequencing in both diagnostic and research settings, it has become desirable to be able to both map autozygous regions and identify the deleterious variants using a single dataset. We have developed AgileMultiIdeogram, an application that can identify and visualize autozygous regions in inbred individuals using exome data as well as microarray SNP genotype data. This application has been successfully used in both research and diagnostic settings to map pathogenic mutations.